Analysis of the Science Concept Understanding of Inclusive Students in Junior High Schools - Hestiningtyas Yuli Pratiwi; Kristanti Diana Malo; Indriyani Rachman; Ida Hamidah; Anna Permanasari; Ade Gafar Abdullah; Muhammad Nur Hudha (Universitas Muhammadiyah Sidoarjo, 2020)
This research focuses on discussing the learning and understanding of the concepts of science in inclusive students at one of the State Junior High Schools in Malang with questionnaire methods, interviews, and documentation. The subjects used in this research were 2 source teachers, 2 special companion teachers (GPK), 25 regular students from class VIIIB, and 14 students with special needs. The learning system, especially with the topic of global warming in the inclusive school, is not yet fully optimal because the learning process is dominated by teachers using the lecture method. The level of understanding of the concept of regular students falls into the good category up to the cognitive domain C4. Meanwhile, the average student with special needs is better able to understand the concept by giving examples in the cognitive domain of C2. The low level of understanding of students' concepts, especially students with special needs, is due to the learning system which is more dominated by teachers in the classroom, the unavailability of learning media for students with special needs in understanding each concept and the number of special companion teachers (GPK) for students who need them which is still limited.